Changes in digestive enzymes activities during the initial ontogeny of wolf cichlid, Parachromis dovii (Perciformes: Cichlidae) - FRIAS QUINTANA, CARLOS ALFONSO (2019)
Wolf cichlid, Parachromis dovii, is a species with a high potential for aquaculture in Central America; however, the knowledge of the digestive physiology in larvae period is limited. For these reason, this study evaluated the changes on digestive enzymes (alkaline and acid proteases, trypsin, chymotrypsin, aminopeptidase, carboxypeptidase, lipases, amylases, and phosphatases) during early ontogeny by biochemical analysis. All digestive enzymes were detected at first feeding (6 days after hatching, DAH, 9.49 mm, 168 degree-days DD). Afterwards all enzymes reached two main peaks in activity at 14 or 22 DAH (15.10 mm, 364 DD and 20.83 mm, 550 DD, respectively). Later, there was a gradual decrease in activity for trypsin and acid and alkaline phosphatases until reach the lowest values at 41 DAH. In the case of acid proteases, chymotrypsin, aminopeptidase, carboxypeptidase, lipase and amylase, all activities reached their maximum values at the end of the larval period, except for alkaline proteases, which showed the maximum value at 14 DAH (15.10 mm, 364 DD). Parachromis dovii larvae have an early capability to hydrolyze exogenous food, agreeing with other carnivorous neotropical cichlid species, for this reason we proposed that the weaning process could begin at 14 DAH.